2000
DOI: 10.1046/j.1365-2672.2000.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 16s rRNA and cellular fatty acid profiles as markers of human intestinal bacterial growth in the chemostat

Abstract: Chemostats were used to study the effects of carbon and nitrogen limitation and specific growth rate on 16S rRNA synthesis and cellular fatty acid (CFA) profiles in four human intestinal bacteria (Bacteroides thetaiotaomicron, Bifidobacterium adolescentis, Clostridium bifermentans and Cl. difficile). Cellular fatty acid synthesis varied with dilution rate and nutrient availability in different species, but these cellular constituents were relatively stable phenotypic characteristics in Bact. thetaiotaomicron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…To our knowledge, this investigation is the first to demonstrate that SRB can be detected in the stools of very young infants (0–6 months of age). With respect to DNA quantitation, desulfovibrio populations were found to be significantly lower in the stools of this group than in elder infants, although this was not consistent with the RNA analysis, which also gives an indication of metabolic activity [44]. This emphasises an important difference between the two techniques: with real‐time PCR, a specific measure of cell number is achievable, while northern hybridisations give a value that is a percentage of total bacterial 16S rRNA in a sample.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, this investigation is the first to demonstrate that SRB can be detected in the stools of very young infants (0–6 months of age). With respect to DNA quantitation, desulfovibrio populations were found to be significantly lower in the stools of this group than in elder infants, although this was not consistent with the RNA analysis, which also gives an indication of metabolic activity [44]. This emphasises an important difference between the two techniques: with real‐time PCR, a specific measure of cell number is achievable, while northern hybridisations give a value that is a percentage of total bacterial 16S rRNA in a sample.…”
Section: Discussionmentioning
confidence: 61%
“…Vlaeminck et al (2006) reported that odd-and branched-chain fatty acids in milk fat are largely derived from bacteria leaving the rumen. These fatty acids can be found in animal tissues, especially those of ruminants, and their content can often be used as a taxonomic marker (Hopkins and Macfarlane 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Identi®cation according to this method is based upon comparison with a library of FAME pro®les for bacteria grown in identical conditions. The technique is used routinely in this laboratory for the identi®cation of EFFECT OF CARBOHYDRATES ON BIFIDOBACTERIA bacteria at the genus and often the species level [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Probe groups targeted were total bacterial rRNA, a Bi®dobacterium genus probe, and a probe for the enterobacterial group. Synthetic HPLC-puri®ed oligonucleotide probes were 59 end-labelled with 32 P by means of polynucleotide kinase (Gibco BRL) and [ã-32 P] ATP (ICN, The Netherlands) with a speci®c activity of .5000 Ci/ mmol and a concentration of 10 mCi/ml, as described previously [16].…”
Section: Rrna Extraction and Oligonucleotide Probe Hybridisationmentioning
confidence: 99%